2002
DOI: 10.1107/s0108767302015556
|View full text |Cite
|
Sign up to set email alerts
|

The generalizedFconstraint in the maximum-entropy method – a study on simulated data

Abstract: One of the classical problems in the application of the maximum-entropy method (MEM) to electron-density reconstructions is the uneven distribution of the normalized residuals of the structure factors jF obs Hj À jF calc Hja'H of the resulting electron density. This distribution does not correspond to the expected Gaussian distribution and it leads to erroneous features in the MEM reconstructions. It is shown that the classical 1 2 constraint is only one of many possible constraints, and that it is too weak to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…Therefore, electron-or nuclear-density distributions in real space smooth down with increasing order, x (de Vries et al, 1994;Palatinus and van Smaalen, 2002). Weighting of d j 4 is reported to be the best in the case of single-crystal X-ray diffraction (de Vries et al, 1994).…”
Section: Mpf Analysis Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, electron-or nuclear-density distributions in real space smooth down with increasing order, x (de Vries et al, 1994;Palatinus and van Smaalen, 2002). Weighting of d j 4 is reported to be the best in the case of single-crystal X-ray diffraction (de Vries et al, 1994).…”
Section: Mpf Analysis Guidelinesmentioning
confidence: 99%
“…Dysnomia further adopts a linear combination of generalized F constraints (Palatinus and van Smaalen, 2002):…”
Section: Procedures Of Structure Refinementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous publication (Palatinus & van Smaalen, 2002), we have investigated these problems and it was demonstrated that the MEM with a uniform prior leads to artifacts that are larger than the differences between the true electron density and the electron density of a procrystal that is based on spherical atoms. A new constraint was proposed that is based on the higher-order central moments of the distribution of F MEM H À F obs Ha'H.…”
Section: Introductionmentioning
confidence: 99%